Modeling of fermentative polyhydroxyalkanoate production from Cerbera odollam oil using Monod-based and multi-scale kinetic models - Lim, Sook Wei; Jibrail Kansedo; Tan, Inn Shi; Jobrun Nandong; Tan, Yie Hua; Lam, Man Kee; Clarence M. Ongkudon (Elsevier, 2025)
Two mathematical models were developed to elucidate the biosynthesis of polyhydroxyalkanoates (PHAs) by Pseudomonas resinovorans DSM 21078 from Cerbera odollam oil – (1) The modified Monod-based kinetic model was integrated with Andrews, Haldane, and Logistic kinetics to describe carbon, nitrogen, and self-inhibition effects on cell growth and PHA production. An additional nitrogen regulatory factor was incorporated to account for urease activity and alternative nitrogen sources during fermentation. (2) The multi-scale kinetic model was adapted to capture three dynamic modes in the biosynthesis process (i.e., using Triple First-Order model), namely fast and slow modes of PHA production, and PHA degradation mode. The fast factors could be prompted by the de novo fatty acid synthesis pathway, saturated fatty acids in the oil compounds, and late-exponential-phase cells in the culture. Overall, the established mathematical models offered a robust predictive framework, providing valuable insights into fermentation behaviour that could advance oil-based PHA production systems.